2016
DOI: 10.1049/el.2016.0693
|View full text |Cite
|
Sign up to set email alerts
|

PCB‐integrated thin film thermocouples for transient temperature measurement

Abstract: A thin film thermocouple (TFTC) on printed circuit board (PCB) substrate is investigated for measuring transient high temperature. The thermal conductivity of PCB is smaller than that of ceramic, which indicates less influence of substrate on heat conduction of TFTC. Therefore, PCB is suitable to make fast response sensors although it cannot withstand continuous high temperature as ceramic. On the other hand, the TFTC is fabricated on the PCB with measurement circuit together, which integrates a miniature meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Both well-known resistive and thermocouple sensors can measure the temperature of the top oil in a transformer [63]. In the case of the resistance thermometer, changes in the resistance due to the temperature are measured to define the temperature.…”
Section: Thermocouple and Resistive Sensorsmentioning
confidence: 99%
“…Both well-known resistive and thermocouple sensors can measure the temperature of the top oil in a transformer [63]. In the case of the resistance thermometer, changes in the resistance due to the temperature are measured to define the temperature.…”
Section: Thermocouple and Resistive Sensorsmentioning
confidence: 99%
“…In 2016, Satish et al used a nickel-based alloy as the base to prepare K-type thermocouples by vacuum coating technology [19]. Wang et al made a high temperature transient heat flux sensor using the printed circuit process, and found that the sensor made based on the printed circuit process has a higher response speed than the sensor based on ceramics [20].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement plays an important role in science, industry, and commerce. The influence of metrology can be felt in technics [1], [2], technology [3], [4], economy [5], [6] and science [7]- [9], as well as in the fields of public health and safety [10], law and legal system and forensic studies [11], and in many others. Thus, it is no wonder that a considerable share of GDP in the developed countries belongs to the field of metrology and adjacent fields [12].…”
Section: Introductionmentioning
confidence: 99%